Clinically Improvement in a Case of COVID-19 with Gastrointestinal Manifestations through Using Natural Therapy Based on Persian Medicine: A Case Report - Marzieh Beygom Siahpoosh (Tehran University of Medical Sciences, 2020)
In addition to respiratory symptoms as the most common manifestations of COVID-19, GI tract symptoms may occur in some patients, as well. These symptoms could be disabling and annoying and supportive treatments are required to control them. Some natural remedies based on Persian medicine could be effective to fast control of GI manifestations of COVID-19 disease through Food modification and using some medicinal plants and Life style correction. This paper reports a case of COVID-19 patient with GI complications which has been treated by using Persian Medicine recommendations.